Relation Between Anemia and ABO Blood Group in Pregnant Women: Retrospective Observational Study in Tobruk, Libya - Mohammed, Asmai; Sabrien Aboubakr,; Brijesh Kumar,; Fatma Abad,; Moftah Hussain, (AlQalam Journal of Medical and Applied Sciences, 2024)
Anemia is one of the most common complications related to pregnancy. Normal physiologic changes in pregnancy affect the hemoglobin (Hb), and there is a relative or absolute reduction in Hb concentration. The purpose of this study was to evaluate the incidence of anemia among pregnant women and its relation to blood group and occurrence of anemia, so that preventive measures can be taken to combat anemia in women who are more susceptible to it. The retrospective study was conducted on 2469 pregnant who are in the age group of 18-45 years in Tobruk Medical Center. Blood samples were determined using tube method using antisera A, B and D and the Hemoglobin concentration analysis was estimated using Sysmex XP-300. In our study we found that women with blood group A+ and O+ (36%) were more prone for anemia, followed by B+ (20%), AB+ (7 %). Chi-square value exhibited 26.538 with a p-value of 0.143 which was showing non-significant (> 0.05) association between anemia and all blood groups. We can conclude that pregnant with blood groups A and O were more prone to anemia followed by blood group B and least with blood group AB. Additional research is required to determine the causes and related factors of anemia among pregnant women. The exact mechanisms behind the relationship between ABO blood group and anemia are not fully understood. However, it is hypothesized that the antibodies produced by different blood groups may interact with red blood cells in ways that impact their lifespan or production. Understanding this relationship is crucial for developing targeted interventions to manage anemia in pregnant women, ensuring better maternal and fetal health outcomes. فقر الدم هو أحد المضاعفات الأكثر شيوعًا المرتبطة بالحمل. تؤثر التغيرات الفسيولوجية الطبيعية أثناء الحمل على الهيموجلوبين، ويحدث انخفاض نسبي أو مطلق في تركيز الهيموجلوبين. هدفت هذه الدراسة إلى تقييم معدل الإصابة بفقر الدم بين النساء الحوامل وعلاقته بفصيلة الدم وحدوث فقر الدم، حتى يمكن اتخاذ التدابير الوقائية لمكافحة فقر الدم لدى النساء الأكثر عرضة للإصابة به. أجريت الدراسة بأثر رجعي على 2469 امرأة حامل تتراوح أعمارهن بين 18 و 45 سنة في مركز طبرق الطبي، وتم تحديد عينات الدم باستخدام طريقة الأنبوب باستخدام المصل المضاد A و B و D وتم تقدير تحليل تركيز الهيموجلوبين باستخدام جهاز Sysmex XP-300. في دراستنا وجدنا أن النساء من فصيلة الدم A+ و O+ (36%) كن أكثر عرضة للإصابة بفقر الدم، يليهن B+ (20%) و AB+ (7%). أظهرت قيمة مربع كاي 26.538 مع قيمة p 0.143 والتي أظهرت ارتباطًا غير مهم (> 0.05) بين فقر الدم وجميع فصائل الدم. يمكننا أن نستنتج أن الحوامل من فصيلة الدم A و O أكثر عرضة للإصابة بفقر الدم، يليهن فصيلة الدم B وأقل عرضة للإصابة بفصيلة الدم AB. هناك حاجة إلى مزيد من البحث لتحديد أسباب وعوامل فقر الدم المرتبطة به بين النساء الحوامل.إن الآلية الدقيقة وراء العلاقة بين فصيلة الدم ABO وفقر الدم ليست مفهومة بالكامل. ومع ذلك، يُفترض أن الأجسام المضادة التي تنتجها فصائل الدم المختلفة قد تتفاعل مع خلايا الدم الحمراء بطرق تؤثر على عمرها أو إنتاجها. إن فهم هذه العلاقة أمر بالغ الأهمية لتطوير تدخلات مستهدفة لإدارة فقر الدم لدى النساء الحوامل، وضمان نتائج أفضل لصحة الأم والجنين